Reference ranges of CT quantitative indexes based on paired inspiratory and expiratory chest CT in healthy Chinese adults: A community-based cohort study - Ziwei Zhang; Xiuxiu Zhou; Yi Xia; Qianxi Jin; Yu Guan; Taohu Zhou; Yueze Li; Shiyuan Liu; Li Fan (Meta-Radiology)
Purpose: Computed tomography (CT) screening has established itself as the routine method to monitor lung conditions by providing pulmonary structural and functional information. However, the reference ranges of CT indices are still lacking. Therefore, this study aimed to provide reference ranges for CT quantitative indexes in healthy middle-aged and elderly Chinese population. Materials and Methods: A total of 783 healthy Chinese adults attending our hospital for the NELCIN-B3 protocol were enrolled. Paired inspiratory and expiratory chest CT and pulmonary function tests (PFTs) were performed in all subjects, CT indices based on density and parametric response map (PRM) were obtained, and PFTs and CT data were retrospectively collected. The reference range was obtained with the Lambda-Mu-Sigma model. Independent-sample t-test/one-way ANOVA analysis or Mann-Whitney test/Kruskal-Wallis test were conducted to compare mean values between different groups. Spearman correlation analysis was used to evaluate the correlation between spirometric and CT quantitative indices. Results: A total of 783 healthy subjects (255 men, 67 (63–69) years) were included. The reference ranges of lung volume, the percentage of low attenuation area (LAA (%)), PRMEmphy (%) and PRMfSAD (%) concerning age based on gender were established. LAA (%), PRMEmphy (%) and PRMfSAD (%) were significant higher in the upper lobes than in the lower lobes. There was a strong positive correlation between PRMEmphy (%) and PRMfSAD (%) (r ​= ​0.62, p ​< ​0.001). Conclusions: We established Chinese reference ranges for CT quantitative indexes in the population aged from 40 to 75 years old.